Anti-aging effects of polysaccharides from quinoa (Chenopodium quinoa Willd.) in improving memory and cognitive function. (July 2022) - Hu, Yichen; Zhou, Jie; Cao, Yanan; Zhang, Jinming; Zou, Liang
Graphical abstract: A polysaccharide from Quinoa (Chenopodium quinoa Willd.) exhibits the remarkable suppression effect on brain aging to improve memory and cognitive function. Highlights: The extracted QP was characterized by both 1 H NMR and FT-IR spectrum. QP could improve the memory and cognition function of D-gal-induced aging mice. The anti-aging effects of QP may involve the regulation of SITR1-associated pathway. Abstract: Given that the polysaccharide of Quinoa ( Chenopodium quinoa Willd., QP) exhibited preliminarily antioxidant activity in our previous studies, herein its anti-aging activities being associated with the antioxidant effect were evaluated in vitro and in vivo . A series of characterization including 1 H NMR spectra, FT-IR spectra, and monosaccharide composition analysis, were implemented, indicated that homogalacturonans might exist as the major polysaccharide fraction in QP. The in vitro antioxidant assay demonstrated that QP had superior scavenging activities on DPPH and ABTS + . Oral administration of QP (100, 400, and 800 mg·kg −1 ) to D-galactose-induced mice significantly ameliorated the learning and memory of aging mice in the Morris water maze test. Meanwhile, QP could alleviate oxidative stress in brain and liver tissues, possibly related to an increase in antioxidant enzymes, reduction of lipid peroxidation, and restoration of lipid metabolism. The anti-aging effects of QP may involve the regulation of SITR1-associated target proteins including DBC1, p53, and Foxo3a in brain tissues. Overall, we demonstrate that QP would be a promising dietary supplement, which benefit to prevent aging and improve memory as well as cognitive function.